Relapsing polychondritis: A rare cause of sudden severe sensorineural hearing loss - Asha'ari, Zamzil Amin; Razali, Mohd. Sayuti; Yusof, Rosnida Azura (Ministry of Health and Universiti Brunei Darussalem, 2013)
Relapsing polychondritis (RP) is a very rare diseas e, and the symptoms can be vague. This case report serves as a reminder to take RP into consideration in patients with sudden hearing loss, with concur rent features of recurrent cartilaginous inflammati on. A young lady presented with recurrent eye in flammation for two years and sought treatments from various general practitioners and ophthalmolo gists. Each attack was successfully controlled with a short course of oral or topical steroids. She la ter developed sudden onset aural perichondritis and sev ere bilateral sensorineural hearing loss and a diag nosis of RP was made after clinical and laboratory assessments. Delay in the diagnosis and treatment has led to permanent hearing loss in this patient.